Pengaruh Citra Merek, Harga, Dan Kualitas Produk Indomie Melalui Kepuasan Konsumen Sebagai Variabel Intervening Terhadap Loyalitas Pelanggan - Putiari Alaina Rizki; Budi Prabowo (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Instant Noodle is a food product that is practical and much-loved by all people. Therefore, companies need to analyze consumer behavior towards the pattern of purchasing their products. This study aims to determine the effect of brand image, price, and quality of Indomie products through consumer satisfaction as an intervening variable on customer loyalty. The number of samples is 100 respondents. The data analysis technique used was path analysis with the help of the SPSS 25.0 program. Sobel test results show that there is an influence between brand image on customer loyalty through customer satisfaction as an intervening variable, price on customer loyalty through customer satisfaction as an intervening variable, and product quality on customer loyalty through customer satisfaction as an intervening variable. This is because the value of t count is greater than t table. Keywords: Brand Image, Price, Product Quality, Consumer Satisfaction, Customer Loyalty